ANALISIS Cd PADA SEDIAAN EYESHADOW DARI PASAR KIARACONDONG BANDUNG - Fenti Fatmawati (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2017)
In this research has been done cadmium analysis (Cd) on eyeshadow cosmetics derived from Kiaracondong Market Bandung City with Atomic Absorption Spectrophotometric method. Samples were taken at random from the registered and unregistered. The purpose of this research is to determine the content of cadmium metal (Pb) on eyeshadow cosmetic obtained from Kiaracondong Bandung market and to determine the safety of the eyeshadow with reference to BPOM regulation. Based on the result of research, we obtained the data that content of cadmium on unregistered eyeshadow sample that is 1,018; 0.720 and 0.805. The content of cadmium on registered eyeshadow samples that is 0.371; 1,631 and 1,161 bpj. All samples, whether registered or unregistered, can be declared safe Kata kunci: Cadmium, eyeshadow, AAS validation methode